Kajian Mantra Da Bei Zhou untuk Menumbuhkan Keyakinan dalam Diri Umat Buddha - Boniran Boniran (STABN Sriwijaya, 2019)
The Da Bei Zhou Mantra is one of the most popular mantras among Buddhists especially the Mahayana sect who always recite this mantra at Ce It and Cap Go. This is done by the Mahayana Buddhists especially with the aim of obtaining blessing, health and always getting protection from the gods, in order to avoid danger. The practice of reciting the mantra